FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN MINAT WUS DALAM PEMERIKSAAN IVA TEST - Maria Ulfa; Epi Saptaningrum; Paskalinda M. Y. Bandur; Gita Sandy Patonengan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
In Indonesia, cervical cancer still ranks highest as one of the most common types of cancer experienced by women. Ironically, about 70% of diagnosed cervical cancer cases are in an advanced stage. The purpose of this study was to determine the factors associated with WUS interest in IVA testing. The research design used in this study was cross-sectional. The study was conducted in the Bangetayu Community Health Center working area in April 2025. The study population consisted of married women aged 19-35 years who lived in the Bangetayu Community Health Center working area. The sample consisted of 55 respondents. The sampling technique used was purposive sampling. The research instrument used a research questionnaire. Data analysis was performed using univariate and bivariate analysis. The results showed a relationship between knowledge (p value: 0.003) and husband support (p value: 0.029) with interest in the IVA test. It is recommended that WUS increase their knowledge about cervical cancer so that their attitudes and awareness about the importance of IVA screening improve. Keywords: Husband's Support, Knowledge. WUS